Development of an evidence‐based Evaluation Toolkit for suicide prevention networks in regional Australia. (6th April 2020) - Ferguson, Monika; McIntyre, Heather; Martinez, Lee; Eygenraam, Janice; Baker, Amy; Procter, Nicholas
Abstract: Problem: Suicide is a global public health concern, particularly for those living in rural, regional and remote areas. Despite numerous prevention initiatives, suicide continues to impact individuals, families and communities. Suicide prevention networks are an innovative, community‐based approach to addressing suicide within local government areas. Anecdotally, suicide prevention networks make an important contribution to suicide prevention, yet frameworks for evaluating their impact do not exist. The purpose of this project was to develop an Evaluation Toolkit to be used by suicide prevention networks throughout South Australia to monitor their impact. Design: Participatory action research was used to work with one suicide prevention network in regional South Australia to co‐design and produce the Evaluation Toolkit. Setting: One regional South Australian town, with an established suicide prevention network. Key measures for improvement: The development of an Evaluation Toolkit, to allow all South Australian suicide prevention networks to measure their impact in a consistent manner. Strategies for change: The Evaluation Toolkit has been made freely available in electronic form and as a hard copy booklet for use by all South Australian suicide prevention networks. Effects of change: The purpose of this project was to develop the Evaluation Toolkit. Formal assessment of its usability and effectiveness is yet to be undertaken, but preliminary anecdotal evidence indicates aspects of the Evaluation Toolkit are useful, especially the questionnaire templates that can be adapted and used to evaluate various community events. Lessons learnt: Participatory action research is a useful method for working with community‐based suicide prevention groups.